Establishing a theoretical foundation for measuring global health security: a scoping review - Sanjana J. Ravi; Diane Meyer; Elizabeth Cameron; Michelle Nalabandian; Beenish Pervaiz; Jennifer B. Nuzzo (BMC, 2019)
Abstract Background Since the 2014-2016 West Africa Ebola epidemic, the concept of measuring health security capacity has become increasingly important within the broader context of health systems-strengthening, enhancing responses to public health emergencies, and reducing global catastrophic biological risks. Efforts to regularly and sustainably track the evolution of health security capabilities and capacities over time - while also accounting for political, social, and environmental risks - could help countries progress toward eliminating sources of health insecurity. We sought to aggregate evidence-based principles that capture a country's baseline public health and healthcare capabilities, its health security system performance before and during infectious disease crises, and its broader social, political, security, and ecological risk environments. Methods We conducted a scoping review of English-language scholarly and gray literature to identify evidence- and practice-based indicators and proxies for measuring health security at the country level over time. We then used a qualitative coding framework to identify recurrent themes in the literature and synthesize foundational principles for measuring global health security. Documents reviewed included English-language literature published after 2001 until the end of the research period-September 2017-to ensure relevance to the current global health security landscape; literature examining acute infectious disease threats with potential for transnational spread; and literature addressing global health security efforts at the country level. Results We synthesized four foundational principles for measuring global health security: measurement requires assessment of existing capacities, as well as efforts to build core public health, healthcare, and biosecurity capabilities; assessments of national programs and efforts to mitigate a critical subset of priority threats could inform efforts to generate useful metrics for global health security; there are measurable enabling factors facilitating health security-strengthening efforts; and finally, measurement requires consideration of social, political, and ecological risk environments. Conclusion The themes identified in this review could inform efforts to systematically assess the impacts and effectiveness of activities undertaken to strengthen global health security.